Role of hysteroscopy and ultrasound in early identification of post-molar gestational trophoblastic neoplasia. (November 2020) - Subbaiah, Murali; Raj, Ashwini; Durairaj, Jayalakshmi; Keepanasseril, Anish
Abstract: Objective: To evaluate the role of hysteroscopy and ultrasound in early identification of gestational trophoblastic neoplasia (GTN) after molar evacuation. Methods: This was a prospective study involving 52 women with an ultrasound diagnosis of complete hydatidiform mole, attending a tertiary centre in south India between August 2016 and August 2019. Baseline characteristics such as age, serum beta-human chorionic gonadotropin(β-hCG) level, gestational age, and uterine size were noted. After the evacuation of molar pregnancy, weekly follow-up with β-hCG was performed, until three consecutive values were normal and then monthly for six months. Findings of transvaginal ultrasound and diagnostic hysteroscopy, performed on follow up at three weeks, were noted. Primary outcome was the development of GTN. Area under the curve(AUC) was calculated to assess the usefulness of these methods in early identification of GTN. Results: Thirteen women (25 %) developed GTN during follow up, within 6 months. Twenty six(50 %) cases had high-risk molar pregnancy. Positive findings on hysteroscopy and ultrasonography were noted in 44.2 % and 19.2 % respectively. AUC was 0.83(95 % CI, 0.70−0.97) for ultrasound and 0.82(95 % CI, 0.72–.92) for hysteroscopy. Sensitivity and specificity were 69.2 % and 97.4 % for ultrasound and it was 92.3 % and 71.8 % respectively for hysteroscopy in identifying those who developed GTN on follow-up. Conclusions: Transvaginal ultrasound as well as hysteroscopy may help in early identification of women at risk of developing GTN following a molar evacuation. Being a non-invasive method with similar discriminative value, ultrasonographic evaluation may be used for early identification of women with GTN after validation in future studies.